Super-High Magnification Dermoscopy Can Help for the Diagnosis of Lentigo Maligna: a Pilot Study on 61 Cases - Elisa Cinotti; Alessandra Cartocci; Flavio Giulio Liso; Vittoria Cioppa; Francesca Falcinelli; Linda Tognetti; Pietro Rubegni; Jean Luc Perrot (Mattioli1885, 2023)
Introduction: Facial lentigo maligna/lentigo maligna melanoma (LM/LMM) is a significant diagnostic clinical challenge and dermoscopy can help its diagnosis. Objectives: The following study aimed to evaluate if super-high magnification dermoscopy at 400x can add further details for the diagnosis of the LM/LMM. Methods: This is a retrospective observational, multicentric study enrolling patients who received a 20x and 400x (D400) magnification dermoscopic examination of facial skin lesions in clinical differential diagnosis with LM/LMM. Dermoscopic images were retrospectively evaluated by four observers for the presence/absence of nine 20x and ten 400x dermoscopic features. Univariate and multivariate analyses were carried out to find predictors of LM/LMM. Results: We enrolled 61 patients with a single atypical skin lesion of the face, including 23 LMs and 3 LMMs. The presence of roundish and/or dendritic melanocytes (P < 0.001), irregular arrangement of melanocytes (P <0.001), irregular in shape and size melanocytes (P = 0.002), and folliculotropism of melanocytes (P <0.001) at D400 were more frequent in LM/LMM than other facial lesions. According to the multivariate analysis, roundish melanocytes at 400x dermoscopy were more indicative of LM/LMM (Odds Ratio-OR 49.25, 95% CI 8.75-513.2, P < 0.001), and sharply demarcated borders at 20x dermoscopy were more indicative of not-LM/LMM (OR 0.1, 95% CI 0.01-0.79, P = 0.038). Conclusions: D400 can identify atypical melanocyte proliferation and folliculotropism that can help to identify LM/LMM together with conventional dermoscopy data. Our preliminary observations should be confirmed by larger studies.